Potato Protein-Based Vegan Burgers Enriched with Different Sources of Iron and Fiber: Nutrition, Sensory Characteristics, and Antioxidants before and after In Vitro Digestion - Przemysław Łukasz Kowalczewski; Martyna Maria Wróbel; Krzysztof Smarzyński; Joanna Zembrzuska; Mariusz Ślachciński; Paweł Jeżowski; Aneta Tomczak; Bartosz Kulczyński; Magdalena Zielińska-Dawidziak; Karina Sałek; Dominik Kmiecik (Foods, 2024)
The aim of this research was to develop a technology for the production of plant-based burgers (PBBs) based on potato protein, also containing high content of iron and appropriately selected fats. The produced PBBs were characterized in terms of their nutritional and bioactive properties both before and after the in vitro digestion process. It was found that the produced burger was characterized by high protein content, ranging from 20.80 to 22.16 g/100 g. It was also shown to have a high dietary fiber content, ranging from 8.35 to 9.20 g/100 g. The main fraction of dietary fiber in the tested samples was insoluble fiber, which accounted for approximately 89% of the total fiber content. In addition, noteworthy is the high digestibility of the protein, reaching approximately 95% for the potato fiber used in the formulation, and about 85% for the oat fiber. Produced PBBs also provide significant amounts of iron, with the use of an organic iron source greatly increasing its quantity in the final product. The analyzed antioxidant properties before and after the digestion process showed a tenfold increase in biological activity after digestion, indicating that the examined PBBs may counteract oxidative stress. Analyzing the chemical and biological properties, it is impossible not to assess consumer attractiveness. It has been shown that PBB1, which contains potato fiber and powdered sprouts enriched with ferritin, received the highest attractiveness ratings among respondents.